Human phosphodiesterase 4A: characterization of full-length and truncated enzymes expressed in COS cells. - Owens, R; Catterall, C; Batty, D; Jappy, J; Russell, A; Smith, B; O'Connell, J; Perry, M (1997)
The type 4 phosphodiesterase (PDE) family comprises four enzymes (4A, 4B, 4C and 4D) that are characterized by their specificity for cAMP and selective inhibition by the anti-depressant drug rolipram (4-[3-(cyclopentoxyl)-4-methoxyphenyl]2-pyrrolidone). In common with other PDEs, they consist of a central conserved domain associated with catalytic activity in addition to two N-terminal upstream conserved regions (UCR1 and UCR2) that are unique to the type 4 enzymes. We have isolated a 2 kb cDNA encoding a full-length type 4A PDE{HSPDE4A4B[Bolger, Michaeli, Martins, St.John, Steiner, Rodgers, Riggs, Wigler and Ferguson (1993) Mol. Cell. Biol. 13, 6558-6571]} from a human frontal cortex cDNA library. Northern blot analysis showed that the major PDE4A mRNA of 4.5 kb was widely distributed in different human tissues. The recombinant PDE4A expressed in COS cells had a molecular mass of approx. 117 kDa as revealed by SDS/PAGE/Western blotting with a PDE4A-specific antibody and was specific for cAMP with a Km of 4.8 microM. The enzyme activity was potently inhibited by R-rolipram (IC50 204 nM) and showed a 2.7-fold stereoselectivity over the S enantiomer. Analysis of the kinetics of inhibition indicated that R-rolipram did not behave as a simple competitive inhibitor. Dixon replots suggested that there was more than one mode of interaction consistent with the detection in the enzyme of a high-affinity binding site for R-rolipram with a Kd of 2.3 nM. Truncation of the PDE4A enzyme by deletion mutagenesis showed that neither of the UCRs was required for catalytic activity and identified an approx. 71 kDa core enzyme with a K(m) for cAMP of 3.3 microM. In contrast with the full-length PDE4A, R-rolipram behaved as a simple competitive inhibitor of this form of the enzyme with decreased potency (IC50 1022 nM) and no stereoselectivity. In addition, no high-affinity rolipram-binding site was detected in the truncated enzyme, indicating that this interaction involves sequences upstream of the catalytic domain of the enzyme.